Functions of enzyme domains in 2-methylisoborneol biosynthesis and enzymatic synthesis of non-natural analogs - Gu, Binbin; Liang, Lin-Fu; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2023)
Two aspects of the biosynthesis of the non-canonical terpene synthase for 2-methylisoborneol have been studied. Several 2-methylisoborneol synthases have a proline-rich N-terminal domain of unknown function. The results presented here demonstrate that this domain leads to a reduced enzyme activity, in addition to its ability to increase long-term solubility of the protein. Furthermore, the substrate scope of the 2-methylisoborneol synthase was investigated through enzyme incubations with several substrate analogs, giving access to two C12 monoterpenoids. Implications on the stereochemical course of the terpene cyclisation by 2-methylisoborneol synthase are discussed.
Keywords: biosynthesis; enzymes; isotopes; substrate analogs; terpenes